A facile and surfactant-free route for nanomanufacturing of tailored ternary nanoalloys as superior oxygen reduction reaction electrocatalysts. Issue 10 (26th April 2017) - Hu, Sheng; Cheng, Kangming; Ribeiro, Erick L.; Park, Kiman; Khomami, Bamin; Mukherjee, Dibyendu
Abstract : Laser ablation synthesis in solution-galvanic replacement reaction (LASiS-GRR) enables tuning of elemental ratios and bonding properties for Pt based ternary nanoalloys as ORR electrocatalysts. Abstract : We have synthesized ternary nanoalloys (NAs) of Pt with transition metals (Co, Cu, Ni, Ti, Ru, Mn) as oxygen reduction reaction (ORR) electrocatalysts using our recently developed laser ablation synthesis in solution-galvanic replacement reaction (LASiS-GRR) technique as a facile and surfactant-free nanomanufacturing route. The specific choice of the elemental compositions is driven by the respective target metal/metal salt redox potential gaps as well as the target metal and/or metal oxide solubility in desired acids. The high-energy thermodynamics of the LASiS-GRR process enables control of the sizes, elemental compositions and distributions of the ternary NAs through systematic tuning of the initial metal salt concentration, pH, laser fluence and ablation time. Specifically, the PtCuCo NAs synthesized with an elemental composition of 72 : 12 : 16 (Pt : Co : Cu) exhibit the best ORR catalytic activity. The NAs largely possess a shell–core structure with the shell composed mostly of Pt and a minor amount of Cu, along with a uniformly alloyed PtCuCo core. Mass and specific activities for ORR performance of the NAs indicate a 4- and 6.5-fold improvement, respectively, over the corresponding activities of commercial Pt/C. We attribute the enhanced activity to 1) our surfactant/ligand-free synthesis technique that prevents catalytic site degradation and 2) minor alloying of the second transition metal Cu that shifts back the Pt d-band center to an optimal position between those of Pt and the PtCo binary NAs, thereby tuning their binding affinities for both oxygen and oxygenated species. Finally, this work establishes the versatility of the LASiS-GRR technique through the synthesis of other ternary NAs (PtRuNi, PtCoMn, PtNiTi) that also exhibit reasonably good ORR activities.